Characterizing PUF disk passive air samplers for alkyl-substituted PAHs: Measured and modelled PUF-AIR partition coefficients with COSMO-RS. (February 2016) - Parnis, J. Mark; Eng, Anita; Mackay, Donald; Harner, Tom
Abstract: Isomers of alkyl-substituted polycyclic aromatic hydrocarbons (PAHs) and dibenzothiophenes are modelled with COSMO-RS theory to determine the effectiveness and accuracy of this approach for estimation of isomer-specific partition coefficients between air and polyurethane foam (PUF), i.e., KPUF−AIR . Isomer-specific equilibrium partitioning coefficients for a series of 23 unsubstituted and isomeric alkyl-substituted PAHs and dibenzothiophenes were measured at 22 °C. This data was used to determine the accuracy of estimated values using COSMO-RS, which is isomer specific, and the Global Atmospheric Passive Sampling (GAPS) template approach, which treats all alkyl-substitutions as a single species of a given side-chain carbon number. A recently developed oligomer-based model for PUF was employed, which consisted of a 1:1 condensed pair of 2, 4-toluene-diisocyanide and glycerol. The COSMO-RS approach resulted in a significant reduction in the RMS error associated with simple PAHs and dibenzothiophene compared with the GAPS template approach. When used with alkylated PAHs and dibenzothiophenes grouped into carbon-number categories, the GAPS template approach gave lower RMS error (0.72) compared to the COSMO-RS result (0.87) when the latter estimates were averaged within the carbon-number-based categories. When the isomer-specific experimental results were used, the COSMO-RS approach resulted in a 21% reduction in RMS error with respect to the GAPS template approach, with a 0.57 RMS error for all alkylated PAHs and dibenzothiophenes studied. The results demonstrate that COSMO-RS theory is effective in generating isomer-specific PUF-air partition coefficients, supporting the application of PUF-based passive samplers for monitoring and research studies of polycyclic aromatic compounds (PACs) in air. Highlights: Estimates of partitioning are improved by using isomer-specific predictions. COSMO-RS performs better than the GAPS template for alkyl-substituted PAHs. An oligomeric model for polyurethane foam is effective for PUF modelling. RMS error is significantly reduced by explicitly considering isomers.